2023
DOI: 10.1088/1402-4896/ace08a
|View full text |Cite
|
Sign up to set email alerts
|

Wave breaking amplitudes of Langmuir modes in electron-positron-ion-dusty plasmas

Abstract: In contrast to the conventional studies on low frequency dust acoustic
or dust ion acoustic waves, the investigation is done
here on the wave characteristics of high frequency Langmuir
modes in electron-positron-ion-dusty plasmas. In the wave analysis, the
electrons, positrons, and ions are considered to follow relativistic dynamics. Whereas
negative or positive polarity massive dust grains form a fixed charge neutralizing background.
Within the Sagdeev pseudopot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Thus, the fictitious particle will execute one-dimensional oscillations inside this potential well. In general, the Sagdeev potential is not symmetric owing to differences in masses and temperatures of the various constituents of the plasma [16][17][18][19]. But for our case of a two-temperature EP plasma, it is easily verifiable that the Sagdeev potential U(f) given by equation (24) is indeed symmetric about f = 0 (see curve 2 in figure 3).…”
Section: Derivation Of Wave-breaking Limitmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, the fictitious particle will execute one-dimensional oscillations inside this potential well. In general, the Sagdeev potential is not symmetric owing to differences in masses and temperatures of the various constituents of the plasma [16][17][18][19]. But for our case of a two-temperature EP plasma, it is easily verifiable that the Sagdeev potential U(f) given by equation (24) is indeed symmetric about f = 0 (see curve 2 in figure 3).…”
Section: Derivation Of Wave-breaking Limitmentioning
confidence: 77%
“…, where ω pe denotes the usual electron plasma frequency and k is the corresponding wave-number. Additionally, a lot of research has been done in the recent years in the field of wave-breaking [15][16][17][18][19].…”
mentioning
confidence: 99%
“…It is observed that high density spikes and sawtooth like structure of the electric field are seen when the positive ion density is low (α = 0.5). This is the signature of the wave breaking [30][31][32][33][34][35][36][37]. However, as we increase the value of α we see the occurrence of sinusoidal profile of the electric field.…”
Section: The Electric Field and Density Profile In Pair-ion Electron ...mentioning
confidence: 85%